THE THERMAL-HYDRAULICS ANALYSIS ON RADIAL AND AXIAL POWER FLUCTUATION FOR AP1000 REACTOR - Muh. Darwis Isnaini; Surip Widodo; Muhammad Subekti (Pusat Teknologi Dan Keselamatan Reaktor Nuklir (PTKRN), 2015)
ABSTRACT THE THERMAL-HYDRAULICS ANALYSIS ON RADIAL AND AXIAL POWER FLUCTUATION FOR AP1000 REACTOR. The reduction of fissile material during reactor operation affects reactivity reduction. Therefore, in order to keep the reactor operating at fixed power, it must be compensated by slowly withdrawing the control-rod up. However, it will change the shape of the horizontal/axial power distribution and safety margin as well. The research carries out the calculations of the core thermal-hydraulics to determine the effect of the fluctuations of the power distribution on the thermal-hydraulic AP1000’s parameters and study their impacts on the safety margin. The calculation is done using the COBRA-EN code and the result shows that the maximum heat flux at the Beginning of Cycle (BOC) is 1624.02 kW/m2. This heat flux will then decrease by 22.75% at the Middle of Cycle (MOC) and by 0.29% at the End of Cycle (EOC). The peak fuel centerline temperature at the BOC, MOC and EOC, are 1608.15°C, 1232.15°C, and 1301.75°C, respectively. These temperature differences are caused by the heat flux effects on sub-cooled boiling regions in the cladding surface. Moreover, the value of MDNBRs at the MOC and EOC are 3.23 and 3.00, which are higher than the MDNBR at the BOC of 2.49. It could be concluded that the operating cycle of the AP1000 reactor should be operated in the MOC and the EOC, which will be more safely than be operated in the BOC. Keywords: Core thermal-hydraulics, AP1000, fluctuation of power distribution, COBRA-EN. ABSTRAK ANALISIS TERMOHIDRAULIKA PADA FLUKTUASI DAYA AXIAL DAN RADIAL UNTUK REAKTOR AP1000. Berkurangnya material fisil selama operasi reaktor, mengakibatkan reaktivitas berkurang. Oleh karena itu, agar reaktor tetap beroperasi pada daya yang tetap, maka harus dikompensasi dengan menarik batang kendali ke atas sedikit demi sedikit. Akan tetapi, hal ini akan berakibat pada berubahnya bentuk distribusi daya ke arah horisontal/aksial dan berdampak ke perubahan marjin keselamatan. Penelitian ini melakukan perhitungan termohidrolika teras untuk mengetahui pengaruh fluktuasi distribusi daya pada parameter termohidrolika AP1000 dan mempelajari dampaknya terhadap marjin keselamatan. Hasil perhitungan dilakukan dengan menggunakan kode COBRA-EN dan hasilnya menunjukkan bahwa fluks kalor maksimum pada awal siklus (BOC) sebesar 1624,02 kW/m2 berkurang 22,75% di tengah siklus (MOC) dan berkurang lagi 0,29% di akhir siklus (EOC). Temperatur puncak tengah bahan-bakar di awal, tengah dan akhir siklus adalah sebesar 1608,15°C; 1232,15°C; dan 1301,75°C akibat dari fluks kalor pada daerah kelongsong yang mengalami pendidihan tak jenuh. Sedangkan nilai MDNBR pada tengah dan akhir siklus adalah 3,23 dan 3,00; meningkat dibanding MDNBR pada awal siklus 2,49. Dari hasil tersebut dapat disimpulkan bahwa pada kondisi tengah dan akhir siklus operasi reaktor AP1000 memiliki marjin keselamatan yang lebih baik dibanding kondisi awal siklus. Kata kunci : Termohidrolika teras, AP1000, fluktuasi distribusi daya, COBRA-EN